A new, long-wavelength borondipyrromethene sphingosine for studying sphingolipid dynamics in live cells - Kim, Raehyun (The American Society for Biochemistry and Molecular Biology, 2013)
Sphingolipids function as cell membrane components and as signaling molecules that regulate critical cellular processes. To study unacylated and acylated sphingolipids in cells with fluorescence microscopy, the fluorophore in the analog must be located within the sphingoid backbone and not the N-acyl fatty acid side chain. Although such fluorescent sphingosine analogs have been reported, they either require UV excitation or their emission overlaps with that of the most common protein label, green fluorescent protein (GFP). We report the synthesis and use of a new fluorescent sphingolipid analog, borondipyrromethene (BODIPY) 540 sphingosine, which has an excitation maximum at 540 nm and emission that permits its visualization in parallel with GFP. Mammalian cells readily metabolized BODIPY 540 sphingosine to more complex fluorescent sphingolipids, and subsequently degraded these fluorescent sphingolipids via the native sphingolipid catabolism pathway. Visualization of BODIPY 540 fluorescence in parallel with GFP-labeled organelle-specific proteins showed the BODIPY 540 sphingosine metabolites were transported through the secretory pathway and were transiently located within lysosomes, mitochondria, and the nucleus. The reported method for using BODIPY 540 sphingosine to visualize sphingolipids in parallel with GFP-labeled proteins within living cells may permit new insight into sphingolipid transport, metabolism, and signaling.